Agent-Based Modeling of Tsunami Evacuation at Figueirinha Beach, Setubal, Portugal - Santos, Ângela (2023)
Previous tsunami numerical model results show that the 1755 tsunami reached the Figueirinha beach 35 min after the earthquake, resulting in the inundation of the beach, the parking lot, and two sections of the road on the beach. Thus, an effective evacuation plan for the beach must be identified. However, conducting drills and evacuation exercises is costly and time-consuming. As an alternative, this study develops an agent-based model (ABM) to simulate the evacuation of beach users. The findings from this study reveal that, across the six considered scenarios, it is not feasible to evacuate all beach users in less than 35 min. The results also show there are only two routes available for evacuation—the left and right sides—with the left side offering a shorter evacuation time. However, both evacuation options come with advantages and disadvantages. The results of this study will be disseminated to local stakeholders.